Improvement of technological quality of eucalypt wood by heat treatment in air at 170-200ºC - Esteves, Bruno (2007)
Eucalypt wood is a low value wood considered a non durable species with low dimensional stability, used almost exclusively for pulp and paper or as firewood. The heat treatment was made in an oven in the presence of oxygen during 2 to 24 h and temperatures of 170-200ºC. Mass loss with treatment, equilibrium moisture content, dimensional stability measured as ASE in radial and tangential directions and at 35%, 65% and 85% relative humidity, MOE, bending strength and wettability were determined. Mass loss increased with treatment time and temperature reaching 9.5% for wood treated at 190ºC for 24h. Equilibrium moisture content decreased more than 50% (at 35% relative humidity) reaching a maximum of 61% reduction. At higher air relative humidity the reduction was smaller, 49% and 38% at the most for 65% and 85% relative humidity. Dimensional stability (ASE) increased with maximum values of 88% and 96% in radial and tangential direction, respectively. The improvement was higher for lower relative humidity. There was a reduction on mechanical resistance with heat treatment especially for bending strength that decreased about 20% for 3% mass loss, reaching 60% for mass losses higher than 10%. MOE decreased with heat treatment the reduction was under 10% until 8% mass loss. The contact angle increased until 5% mass loss, decreasing slightly afterwards. Heat treatment was shown to be a useful method to improve the technological quality of eucalypt wood as regards dimensional stability allowing it to compete with higher cost woods for some applications.